Which Jobs Are Done from Home? Evidence from the American Time Use Survey - Lena Hensvik; Thomas Le Barbanchon; Roland Rathelot (Institute of Labor Economics (IZA), 2020)
Which jobs are more likely to be affected by mobility restrictions due to the Covid-19 pandemic? This paper uses American Time Use Survey data to measure the share of the work hours that are spent at home for different job categories. We compute and provide home-working shares by occupation (US census classification, SOC and international ISCO classification), and by industry (US census classification, NAICS and international ISIC classification).
Keywords: J22; 330; home-working; remote work; time-use; COVID-19